Zr4-Substituted polyoxometalate dimers decorated by d-tartaric acid/glycolic acid: syntheses, structures and optical/electrochemical properties. Issue 5 (8th January 2019) - Ni, Zhi-Hui; Li, Hai-Lou; Li, Xu-Yan; Yang, Guo-Yu
Abstract : Two Zr4 -sandwiched Keggin polyoxometalates functionalized by chirald -tartaric acid and glycolic acid were hydrothermally synthesized and structurally characterized. Their optical and electrochemical properties have been investigated in detail. Abstract : In this article, two new tetra-Zr(iv )-substituted sandwich-type Keggin polyoxometalates functionalized by chirald -tartaric acid and glycolic acid, K2 H10 [Zr4 (H2 O)2 (μ-OH)(μ3 -O)2 (d -tartH)(GeW10 O37 )2 ]·27H2 O (1, D-tartH4 =d -tartaric acid) and K2 H10 [Zr4 (H2 O)2 (μ3 -O)2 (gly)2 (GeW10 O37 )2 ]·32H2 O (2, glyH2 = glycolic acid), have been synthesized under hydrothermal conditions and characterized by FT-IR spectra, elemental analysis, single-crystal X-ray structure analysis, powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA), ultraviolet-visible absorption spectroscopy (UV-vis) and cyclic voltammetry (CV). The structure analysis reveals that both1 and2 contain a [Zr4 (H2 O)2 (μ3 -O)2 (GeW10 O37 )2 ] cluster. UV-vis spectra indicate that both compounds are a wide-gap semiconductor. In addition, compound1 is a chiral Zr(iv )-substituted sandwich-type Keggin cluster because thed -tartH ligand is chiral and the Flack divisor of1 is 0.00, showing non-linear optical properties. The cyclic voltammograms indicate that compounds1 and2 have good electrocatalytic activity in the reduction of H2 O2 .